Corrosion performance of Ni-Cr-Fe alloys in geothermal hypersaline brines - Moeller, R. H.; Cron, C. J. (Nickel Institute, 1998)
This paper discusses the corrosion effects of the brine on the various alloys for lengthy periods under actual flowing conditions. Long-term corrosion tests were also conducted on alloys considered for injection tubing.